Consumer protection mechanisms in the real estate field (مجلة أبحاث قانونية, 2023)
The crisis in the real estate market, revealed by the National Federation of Real Estate Developers according to a press release from the latter, raises more than one question about the legal and economic status of the real estate consumer, especially since the said federation has sounded the bell. alarm on many aspects related to real estate heritage, production and consumption, which requires the search for consumer protection guarantees in the real estate field.
Keywords: consume; the buyer; seller; -Warranties; protection